Periodically scheduled burst flows in optical burst switching networks. (15th October 2008) - Lei, Li; Sampalli, Srinivas
Providing flexible quality of service (QoS) for multiple classes of traffics is one of the important challenges in the design of optical burst switching (OBS) networks. In this paper, we propose a novel bandwidth reservation scheme for periodically scheduled bursts. Multi-protocol label switching (MPLS) is used to construct reliable burst delivery channels across the network. Meanwhile, best effort bursts are transferred using one-way offset signalling to improve the wavelength efficiency. Our hybrid OBS architecture provides flow level QoS control without compromising the performance of best effort bursts. Simulation results show that our approach is better than early dropping schemes.